Perceived Adequacy of School Environment and Waste Management Resources Among Secondary School Students in Baiji District, Iraq: A Cross-Sectional Study: IN PRESS - Sabah Ramadhan Hassan; Nazar Ahmed Mahmood (Jurnal Ilmu Kesehatan Masyarakat, 2026)
Waste management is an important component of a safe and healthy school environment. Inadequate waste-management infrastructure and educational resources may contribute to environmental and health risks among students. This study aimed to assess students’ perceptions of the school environment and resources available for waste management in public secondary schools in Baiji District, Iraq. A school-based cross-sectional study was conducted among 427 students selected through a multistage sampling procedure. Data were collected from November 30 to December 21, 2025, using a structured self-administered questionnaire consisting of six items assessing waste-management facilities, educational activities, policies, and human resources. Descriptive statistics were used to summarize the findings. Overall, 190 students (44.5%) perceived their school environment and waste-management resources as inadequate, 110 (25.8%) as acceptable, and 127 (29.7%) as adequate. Separate bins for recyclable waste were reported as unavailable by 60.2% of students, while 59.3% reported the absence of posters or signs regarding waste disposal. In contrast, 57.6% reported the presence of a clear school waste-disposal policy, and 57.1% reported that their schools organized cleaning activities or lessons. These findings indicate important gaps in waste-management infrastructure and educational resources in the surveyed schools. Strengthening waste-separation facilities, environmental education materials, school waste-management policies, and coordination with municipal waste services may help improve waste-management practices in secondary schools.